The influence of the show and tell learning method on speaking skills in class IV students learning Indonesian Elementary School of Kebayoran Lama Selatan 12 - Ritonga, Rudi (Academy of Education Journal, 2024)
This research aims to find out how influential the application of the show and tell learning method is on the speaking skills of class IV students at SDN Negeri Kebayoran Lama Selatan 12. The method used in this research is experimental. The research started from observations and interviews at school and then formulated a problem formulation with references from several journals, e-books and books. then continued with trials and comparing learning outcomes using conventional methods and after using the show and call method. From the results of the research, it can be seen that the number of students whose scores did not reach KKM in speaking skills using conventional learning and then using the show and tell method was 19 students, decreasing to 5 students with a percentage of 56%. Then further research was carried out using the show and tell method to obtain successful results. students 71.42% of which the value increased 15.42%.